(untitled) (Oratio Directa, 2025)
This article compares Mitsuo Nakamura's study of Muhammadiyah in Kotagede with Mark R. Woodward's study of Javanese Islam. It uses textual analysis of their published ethnographic works and supporting literature. Nakamura traces continuous Islamization through Muhammadiyah's organizational history, Dutch archives, local documents, and publications, emphasizing reform, normative piety, and changing attitudes toward Javanese traditions. Woodward combines participant observation with court manuscripts and Javanese Islamic texts to argue that Javanese Islam is rooted in Islamic law and Sufism rather than being merely a deviation or residual syncretism. The comparison shows different but intersecting trajectories: reformist purification remains embedded in Javanese social life, while Javanese Islamic practices creatively synthesize religious teachings and local cultural forms. Wayang, slametan, court literature, and mystical traditions become contested sites of interpretation rather than fixed evidence of either purity or deviation. The article concludes that the encounter between Islam and Javanese culture is historical, dialogical, and unfinished. Because the analysis relies on two major monographs and selected supporting texts, its claims should be treated as interpretive comparison rather than comprehensive representation of all Javanese Muslim communities.